Direct Observations Reveal the Deep Circulation of the Western Mediterranean Sea. Issue 12 (20th December 2017) - Send, Uwe; Testor, Pierre
Abstract: Direct observations of the deep water circulation in the western Mediterranean Sea are presented, based on the analysis of autonomous profiling floats drifting at 1, 200 and 1, 900 m depth during the 1997–2002 period. The amount of water circulating in the basin is quantified, revealing several distinct gyres and boundary currents. It was also possible to follow the spreading of the newly formed Western Mediterranean Deep Water (nWMDW) and Tyrrhenian Deep Water (TDW), two main components of the deep water in the western Mediterranean, from their origin, based on their temperature and salinity signature. Both boundary currents and isolated eddies carrying the water into the interior are important for this. Key Points: The deep circulation in the Mediterranean Sea is revealed by profiling floats Multiannual average transports in the deep layers were estimated The spreading of the Western Mediterranean Deep Water and the Tyrrhenian Deep Water is characterized